2009
DOI: 10.4269/ajtmh.2009.09-0238
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of and Influences on Timely Administration of Hepatitis B Vaccine Birth Dose in Remote Rural Areas of the People’s Republic of China

Abstract: Abstract.A survey was conducted in 2006 to assess the coverage and timeliness of the birth dose of hepatitis B vaccine (HepB 1 ) and related influences among children in rural areas of Guangxi, Guizhou, Tibet, and Shaanxi provinces, People's Republic of China. A total of 3,390 children born in 2004 were surveyed in four counties in each province, where a project to strengthen routine immunization is being implemented by the China Ministry of Health, supported by the United National Children's Fund. Two-stage s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 15 publications
(22 reference statements)
3
15
0
Order By: Relevance
“…Timeliness of vaccine administration is a problem in many countries for different vaccines and can lead to immunity gaps among those at highest risk for the disease. [16][17][18][19][20][21][22][23] In this survey, we found that timeliness of receipt of all three doses could be improved. Timely BD coverage was < 80% among CP students in three of 29 schools.…”
Section: Discussionmentioning
confidence: 99%
“…Timeliness of vaccine administration is a problem in many countries for different vaccines and can lead to immunity gaps among those at highest risk for the disease. [16][17][18][19][20][21][22][23] In this survey, we found that timeliness of receipt of all three doses could be improved. Timely BD coverage was < 80% among CP students in three of 29 schools.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of total anti-HBc was high in all three communities, but with significant differences between villages and age of the individuals, whereas the prevalence of HBsAg was independently associated with the presence of a household of an HBeAg-reactive carrier. This indicates that, in this region, the condition of being a chronic HBV carrier, despite being associated with early age at which the infection occurs, 40 is probably also associated with the frequency and intensity of contacts with HBV. 41 The characteristics of the potential transmitters (HBeAgreactive and with a high HBV viral load) suggests that transmission occurs mainly in early ages and within a household as they cluster in families.…”
mentioning
confidence: 92%
“…When midwifery and obstetric staff were given the responsibility to administer hepatitis B birth dose vaccination to newborns delivered in health facilities, surveys in central and eastern provinces found 73% and 82% birth dose coverage respectively, while western provinces had only 50% coverage [10]. An assessment conducted in rural areas of four western provinces reported that a major reason for low coverage was poor coordination between immunization and hospital midwifery staff [11]. A similar conclusion was made from an assessment in Vietnam [12].…”
Section: Discussionmentioning
confidence: 70%